Relationship between Emotional Intelligence and Student Self-Control - Wardianto, Ridho; Syukur, Yarmis (Current Issues in Counseling, 2021)
Education plays an important role to improve the quality of a nation. The quality of a nation is marked and measured by the progress of education and its own human resources. Meanwhile, the quality of education in Indonesia currently shows an unsatisfactory situation, the main problems in education are the presence of students who get angry easily, are unable to discuss with colleagues, lack of awareness in doing assignments, lack of empathy and difficulty controlling themselves from criticism. . Therefore, the problem that will be studied in this study is "How self-control can regulate students' emotions to get appropriate learning methods and satisfying achievements". This study aims to describe: (1) students' emotional intelligence, (2) students' self-control and (3) to know and describe the relationship between emotional intelligence and students' self-control at school. This research uses quantitative methods with correlational descriptive research types. The population for this study was 711 students of SMAN 16 Padang Semester January - June 2021/2022. The number of samples is 256 students selected by Stratified Random Sampling. The instruments used were emotional intelligence instruments and self-control instruments using a Likert model scale. Data were analyzed using descriptive statistical techniques and Pearson Product Moment correlation techniques. The findings of this study show that: (1) students' emotional intelligence is in the medium category, (2) students' self-control is in the high category and (3) there is a significant positive relationship between emotional intelligence and self-control with a correlation coefficient value of 0.570 and a significance level 0.004. Implications for guidance and counseling can be carried out by providing information services, individual services and group counseling services.